VOWEL SOUNDS RECOGNITION OF SEVENTH SEMESTER STUDENTS AT STUDY PROGRAM OF ENGLISH UNIVERSITAS BRAWIJAYA USING PHONEMIC RESTORATION EFFECT (PRE) TEST - PUTRI, CELYA INTAN KHARISMA (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: Phonemic Restoration Effect (PRE), top-down processing, bottom-upprocessing, listening strategy Listening skill is one of four main aspects in learning foreign language. Nowadays, university or work entrance exams, exit exams, and other examinations often include listening aspect as an important part of the exams to measure applicant’s foreign language proficiency. In this study, there are two problems of study, they are: (1) What type of listening strategy is mostly used by the 7th semester students of Study Program of English in Faculty of Cultural Studies Universitas Brawijaya in recognizing the vowel sounds and (2) What are the main factors causing difficulty for 7th semester students of Study Program of English in Faculty of Cultural Studies Universitas Brawijaya in recognizing the vowel sounds.The research belongs to qualitative research. The data are obtained through a Phonemic Restoration Effect (PRE) test and some interviews of 28 seventh semester students of Study Program of English. The data are analyzed from combination between the participants’ test answers and interview transcription.The study reveals that 14 from 28 seventh semester Study Program of English students tend to use top-down processing in doing listening test. However, the most effective strategy for the participants in listening is using both top-down and bottom-up processing at the same time. This study also reveals that the most factor causing difficulty for participants while they are doing listening test is because they still have low level of concentration by reaching 32.14% of students who face that factor.The writer suggests the next researcher to be more cautious in developing the questions of the test. The writer also suggests the students to pay more attention in listening matters and some aspects related to listening proficiency. For instance, they should enrich the vocabulary and doing focus training to practice their ability in concentrating.